How does digital technology innovation drive agricultural sustainability? A mechanism study based on green total factor productivity - Gong, Qitong; Tang, Weixue (Frontiers in Sustainable Food Systems, 2025)
Facing environmental pollution challenges in agricultural production, digital technology innovation—serving as the core driver of China’s “Digital China” strategy—emerges as a promising new force for promoting agricultural green development. This study utilises panel data from 30 Chinese provinces (excluding Hong Kong, Macao, Taiwan, and Tibet) covering 2009–2022, employing the SBM-BML model to measure agricultural green total factor productivity (AGTFP) and applying a two-way fixed effects model to examine the impact of digital technology innovation on AGTFP and its underlying mechanisms. The findings demonstrate a significant positive relationship between digital technology innovation and AGTFP. Digital technology innovation enhances AGTFP primarily through optimising resource allocation. Moderating effect analysis reveals that appropriate environmental regulations can strengthen this positive impact. Heterogeneity analysis further indicates that the enhancing effect of digital technology innovation is more substantial in coastal regions and areas with higher financial development levels. Additionally, the study finds that digital technology innovation can promote local high-quality economic development and help address wastewater discharge issues by improving AGTFP. These research findings provide both theoretical foundations and practical guidance for China to better advance agricultural green development in the era of digital intelligence.